2015
DOI: 10.1007/s00421-015-3245-2
|View full text |Cite
|
Sign up to set email alerts
|

Muscle damage, inflammatory, immune and performance responses to three football games in 1 week in competitive male players

Abstract: In summary, post-game performance recovery and inflammatory adaptations in response to a three-game weekly microcycle displayed a different response pattern, with strong indications of a largest physiological stress and fatigue after the middle game that was preceded by only a 3-day recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
195
3
34

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(252 citation statements)
references
References 68 publications
20
195
3
34
Order By: Relevance
“…In the present study, the reduced perception of muscle soreness following acute exercise when n-3PUFA were added to a mixed ingredient beverage did not appear to be mediated by a reduced systemic inflammatory response to exercise. Consistent with previous studies that utilised a simulated soccer matchplay protocol (Mohr et al, 2016), serum CRP concentrations increased 24 hours post-exercise before returning to baseline levels after 48 hours. However, no difference in serum CRP concentrations were reported during acute exercise recovery between test drink conditions.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, the reduced perception of muscle soreness following acute exercise when n-3PUFA were added to a mixed ingredient beverage did not appear to be mediated by a reduced systemic inflammatory response to exercise. Consistent with previous studies that utilised a simulated soccer matchplay protocol (Mohr et al, 2016), serum CRP concentrations increased 24 hours post-exercise before returning to baseline levels after 48 hours. However, no difference in serum CRP concentrations were reported during acute exercise recovery between test drink conditions.…”
Section: Discussionsupporting
confidence: 89%
“…In elite soccer players, knee range of motion was reduced until 48 hours postmatch. 43 Similarly, Mohr et al 54 found knee-joint range of motion declined 7% at both 24 and 48 hours postmatch. Moreover, structural assessments quantifying hip/groin extensibility have shown good reliability and validity after match play in youth soccer players.…”
Section: Joint Range Of Motion/flexibilitymentioning
confidence: 88%
“…In addition, during the inflammatory process, the blood flow velocity is reduced, which allows the interaction of circulating cells with endothelial cells expressing surface molecules capable of binding to leukocytes [5]. It is also important to note that during exercise and post-exercise there is a release of proinflammatory cytokines TNF-α, IL-1β and IL-6 that can remain elevated for a period of 24-48 hours [6], and concomitantly act as endogenous pyrogens, thus contributing to the increase of the internal temperature [5].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, during the inflammatory process, the blood flow velocity is reduced, which allows the interaction of circulating cells with endothelial cells expressing surface molecules capable of binding to leukocytes [5]. It is also important to note that during exercise and post-exercise there is a release of proinflammatory cytokines TNF-α, IL-1β and IL-6 that can remain elevated for a period of 24-48 hours [6], and concomitantly act as endogenous pyrogens, thus contributing to the increase of the internal temperature [5].Considering the factors that trigger the inflammatory process, which consequently alter the skin temperature, it has been proposed the assessment of skin temperature through IRT as an indirect way of measuring muscle damage caused by different types of exercise, especially those with eccentric characteristics. Therefore, the use of IRT can be used as a noninvasive way of measuring body's responses (heat) to the inflammatory process, and can provide valuable information about how the external load was assimilated by the athlete.…”
mentioning
confidence: 99%